PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI APOTEK RAFFI FARMA CIKOTOK LEBAK BANTEN - Putra Pratama, Iqmal; Sulistiani, Sinta (Journal of Research and Publication Innovation, 2024)
This study aims to determine the variable "Effect of Product Quality and service quality on customer satisfaction at Raffi farma pharmacy Cikotok Lebak Banten". The research method used in this study is descriptive with a quantitative approach. The data analysis used includes: Descriptive Statistical Test, Normality, Multicollinearity, Heteroscedasticity, Multiple Linear Regression, t Test (Partial), Test F (Simultaneous), Correlation Coefficient (R) and Coefficient of Determination (R2). The research results from the t test show that the significance value of the 3 independent variables is more than 0.05 with a coefficient of determination (R2). independent variable is more than 0.05, thus it can be concluded that partially both product quality and service quality affect customer satisfaction. service Affects Customer Satisfaction. Meanwhile, from the results of the F test (simultaneous) obtained a significance value of 0.000 (0.000 <0.05) and an Fcount value of 163.866 which means Fcount is greater than Ftable (163.866> 3.094), which means that the variables Product quality and service quality affect customer satisfaction. From the correlation coefficient test results, the value of R value of 0.889 which is the variable Product Quality and Service Quality have a very strong very strong correlation relationship to Customer Satisfaction. And from the results of the coefficient of determination (R2) test, the adjusted R square value value of 0.790, which means that the influence of the variables of Product Quality and Service Quality on Customer Satisfaction in this study is 79.0%, while the rest of the variables of Product Quality and Service Quality on Customer Satisfaction is 0.790.